Molecular Rotors as Reporters for Viscosity of Solutions of Collagen Like Peptides - Barrías-González, P (Royal Society of Chemistry, 2021)
We have studied the suitability of using a molecular rotor-based steady-state fluorometric assay for evaluating changes in both the conformation and the viscosity of collagen-like peptide solutions. Our results indicate that a positive charge incorporated on the hydrophobic tail of the BODIPY molecular rotor favours the dye specificity as a reporter for viscosity of these solutions. © the Owner Societies.